The localization of the alkaloids in Coptis chinensis rhizome by time-of-flight secondary ion mass spectrometry - He, Fan; Huang, Yu-Feng; Dai, Wei; Qu, Xian-You; Lu, Jing-Guang; Lao, Chi-Chou; Luo, Wen-Hui; Sun, Dong-Mei; Wei, Mei; Xiao, Sheng-Yuan; Xie, Ying; Liu, Liang; et al. (Frontiers in Plant Science, 2022)
Understanding the spatial distribution of active compounds can effectively evaluate the quality of decoction pieces of traditional Chinese medicine (TCM). Traditional methods are economical and practical but lack chemical information on the original distribution. Time-of-flight secondary ion mass spectrometry (TOF-SIMS), with the advantage of non-destructive detection of samples, can directly analyze the distribution of chemical compounds on the surface of various samples. In this study, TOF-SIMS image analysis technology was used to detect TCM for the first time. Taking Coptis rhizome (CR) as an example, a commonly used TCM, the distribution of the compounds in the cross-section of CR was studied. Meanwhile, ultra-high-performance liquid chromatography coupled with triple quadrupole mass spectrometry (UPLC-QQQ-MS/MS) was used to verify the results of TOF-SIMS. The distribution of nine active compounds: berberine, epiberberine, coptisine, palmatine, columbamine, jatrorrhizine, tetrahydricheilanthifolinium, and oxyberberine, was well imaged in the cross-section of CR by TOF-SIMS. The content of berberine and epiberberine was the highest; Palmatine distribution in the pith was more than that in other parts; Oxyberberine was mainly concentrated in the cork and xylem rays. Normalization analysis showed contents of these compounds increased along with the growth years. The result was consistent with UPLC-QQQ-MS/MS. In conclusion, the TOF-SIMS method can display the spatial distribution status of the active compounds of herbs, providing a basis for selecting the medicine site with non-destructive and fast detection.